Addressing the Problem of Negative Lexical Transfer Errors in Chilean University Students - Paul Anthony Dissington (Profile Issues in Teachers' Professional Development, 2018)
Studies of second language learning have revealed a connection between first language transfer and errors in second language production. This paper describes an action research study carried out among Chilean university students studying English as part of their degree programmes. The study focuses on common lexical errors made by Chilean Spanish-speakers due to negative first language transfer and aims to analyse the effects of systematic instruction and practice of this problematic lexis. It is suggested that raising awareness of lexical transfer through focused attention on common transfer errors is valued by students and seems essential for learners to achieve productive mastery.